INTEGRATING FREELANCERS AND CONTRACTORS ORGANIZATIONAL STRATEGIES FOR THE FUTURE WORKFORCE - Ridhayantho, Muhamad (Penelitian dan Pengembangan Ilmu, 2024)
This research explores how organizations are integrating freelancers and contractors in their workforce strategies to face the future of an increasingly dynamic world of work. Using a systematic literature review approach, this study analyzes the challenges, strategies and benefits of flexible workforce integration in various sectors. The findings show that although organizations face challenges in maintaining effective culture and collaboration, the integration of a non-permanent workforce increases a company's flexibility and competitiveness. The practical implications of this research provide guidance for HR practitioners to design policies that support a flexible workforce in the context of digital transformation.